Lean Healthcare tools to increase the service level at a Peruvian Maternal and Infant polyclinic - Alvarado-Huamani, Sayuri M. (2022)
Worldwide, there is an increase in the shortage of medical supplies due to the global health situation Covid-19. Therefore, it is important to implement methodologies that improve and optimize the management of medical supplies from their purchase, storage and distribution process within these centers. In this sense, the aim of this article is to analyze the relationship between logistics management, the level of supply of medical centers and the level of service provided to patients. Based on this, a study is made of a maternal and child polyclinic in the city of Lima, which has an availability level of 83.51%, which does not reflect an optimal level. Consequently, classification tools are implemented using the ABC-VED matrix and the Inventory Control System. Complementing it with the application of Good Storage Practices and Lean tools such as 5S and Standardization of work to conclude the proposal for improvement in the logistics management of this particular medical center.